Evaluating the impact of personalized rehabilitation nursing intervention on postoperative recovery of respiratory function among thoracic surgery intensive care unit patients: A protocol for systematic review and meta-analysis. Issue 3 (21st January 2022) - Li, Chun-Yan; Liang, Wen; He, Yan-Qin; Han, Qun
Abstract: Background: Exercise tolerance and lung function can be improved by pulmonary rehabilitation. As a result, it may lower thoracic surgery intensive care unit (ICU) patients' postoperative problems and death. Enhanced recovery after surgery has advanced significantly in the perioperative care of thoracic surgery ICU patients in recent years, and it now plays an essential role in improving ICU patients' postoperative prognosis. Appropriate tailored rehabilitation nursing intervention is required to promote the postoperative recovery of respiratory function in thoracic surgery ICU patients. This study aims to look at the influence of tailored rehabilitation nurse intervention on postoperative respiratory function recovery in thoracic surgery ICU patients. Methods: To find relevant papers, a comprehensive search of electronic databases will be conducted, including three English databases (PubMed, EMBASE, and the Cochrane Library) and two Chinese databases (Chinese National Knowledge Infrastructure and WanFang). Only research that has been published in either English or Chinese will be considered. The retrieval period will run from November 2021 to November 2021. We will look at randomized controlled trials (RCTs) studies that looked at the effect of a customized rehabilitation nursing intervention on the recovery of respiratory function in thoracic surgery ICU patients after surgery. Two writers will review the literature, retrieve study data, and assess the included studies' quality. Any disagreements will be settled via consensus. RevMan 5.3 will be used to do the meta-analysis. Results: This research will offer high-quality data on the influence of customized rehabilitation nurse intervention on postoperative respiratory function recovery in thoracic surgery ICU patients. Conclusion: This study will look at whether a targeted rehabilitation nurse intervention might help thoracic surgery ICU patients recover their respiratory function more quickly after surgery. Ethics and dissemination: There will be no need for ethical approval. Registration number: December 12, 2021.osf.io/9rdu2/ (https://osf.io/9rdu2/ ).